Spectroscopic studies of the reactions of non-aqueous solutions of dichlorobis (N,N'-dibenzylthiourea) cobalt (II) and dibromobis (N,N'-dibenzylthiourea) cobalt (II) with oxidizing and reducing agents) - Prado, Grace Israel (Animo Repository, 1985)
The study deals with the spectroscopic properties of the complexes, dichlorobis (N,N'-dibenzylthiourea) cobalt (II) and dibromobis (N,N'-dibensylthiourea) cobalt (II) in acetone, acetonitrile and absolute ethanol with the addition of the oxidizing and reducing agents. Different concentrations (1.31 x 10-5 M, 2.59 x 10-5 M, and 3.84 x 10-5 M) of the oxidizing and reducing agents were added to the solutions of the complexes in different solvents. It was observed that new absorption bands appear which could be attributed to the formation of a bridged intermediate. The addition of larger amount (3.84 x 10-5 M) of the reagent causes decomposition or complete breakdown of the tetrahedral species as shown by the disappearance of the absorption band in the region, 600-700 nm.